The Role of Spouse Abuse in Couple Burnout: The Balancing Effect of Stress Coping Strategies - Bita Dasarband (Salāmat-i ijtimā̒ī, 2018)
Background and Objective: Spouse abuse is a threatening health crisis the short-term and long-term consequences of which negatively affect women, families and the community. Couple burnout and impaired sexual satisfaction are among adverse consequences of spouse abuse among women. Therefore, the factors need to be defined which can minimize such effects on women’s health. For this purpose, the objective of this study was to determine the effect of strategies in coping with the stress caused by spouse abuse on couple burnout. Materials and Methods: This correlational study was conducted in the city of Tehran in 2015. As many as 302 married women who were selected by convenience sampling method in the 22 districts of Tehran participated in the study. Data were collected through self-administration of the three questionnaires regarding Couple burnout measure, spouse abuse and ways of coping. Statistical analysis was performed using IBM SPSS statistics 22. A probability level of less than 0.05 was considered significant. Results: The mean (SD) of spouse abuse and couple burnout were 11.9 (11.1) and 2.6 (0.9), respectively. Spouse abuse was correlated with couple burnout in women (r=0.55). Women who encountered spouse abuse utilized positive reappraisal, self-control and seeking social support as coping strategies. Among strategies in coping with stress, distancing, positive reappraisal and accepting responsibility had balancing effect on couple burnout among women with previous self-encounter of spouse abuse; Beta coefficient equaled 0.134, 0.125 and 0.117 respectively. Women who utilized positive reappraisal developed less couple burnout. Conclusion:Women who encountered spouse abuse suffer more from couple burnout. Coping strategies including distancing, positive reappraisal and accepting responsibility made women feel less burnout in their marriage.